Elections and CEO successions in Brazilian state-owned companies - Guimarães, Sergio Foldes (2020)
Purpose – To study the impacts of elections and succession processes on SOE stocks. Design/methodology/approach – Through events studies we longitudinally investigate the impacts of political events (elections) and of succession processes on SOE stocks over more than 20 years. We also document changes in management, showing that SOEs face greater turnover in management than their private peers. Stock quotations were obtained from Economática and company and executive data were retrieved from the B3 and CVM. Findings – There is some but not a general impact of elections and succession processes on SOEs. More recently, the impacts have increased. CEO turnover is greater in SOEs than in their private peers and changes in management are greater in cases of power shifts.  Originality/value – We shed light on phenomena that happen frequently in Brazil: CEO successions in SOEs and political events impacting SOEs.